Nailed Through Superior Sagittal Sinus: A Case Report and Surgical Considerations. Issue 3 (18th March 2023) - Kow, Chien Yew; Hakim, Jeffrey S.; Aspoas, A Robert; Brew, Stefan; McGuinness, Ben; Correia, Jason
Abstract : BACKGROUND AND IMPORTANCE: We report a case of nail gun–related penetrating brain injury, puncturing through the anterior third of superior sagittal sinus, which remained patent and was associated with an arteriovenous (AV) shunt revealed on catheter angiogram. CLINICAL PRESENTATION: A previously well 35-year-old male patient presented with a self-inflicted pneumatic nail gun injury. Neurological examination was unremarkable. Computed tomography (CT) of the brain demonstrated the nail had penetrated through the skull, traversed the anterior third of the superior sagittal sinus (SSS), right frontal lobe parenchyma, frontal horn of right lateral ventricle, caudate, and right cerebral peduncle. CT angiogram showed no associated vascular injury, with CT venogram showing a short segment of filling defect within SSS adjacent to nail penetration. However, digital subtraction angiography revealed an associated arteriovenous shunt 8 mm anterior to the dural penetration site, which filled the SSS in arterial phase. Removal of the nail was performed using a double concentric craniotomy around the nail entry site. Before removal of the nail, the SSS anterior to the nail penetration site was tied off and divided along with coagulation and division of the falx, while the SSS posterior to the nail penetration site was also tied off to isolate the penetrated SSS segment. The patient recovered well with repeat digital subtraction angiography demonstrating no residual AV shunting. CONCLUSION: This case report aims to highlight the importance of performing a catheter angiogram and describe our stepwise considerations and approach in treating a penetrating injury involving the superior sagittal sinus with concurrent AV fistula.